Selected endemic zoonoses in pigs presenting for slaughter in Kampala, Uganda - Atherstone, Christine; Mgode, G.F.; Dhand, N.K.; Alonso, Silvia; Grace, Delia; Ward, M.P.; Mor, Siobhan M. (American Society of Tropical Medicine and Hygiene, 2020)
Leptospirosis, brucellosis, and Q fever (coxiellosis) are bacterial zoonoses that cause acute febrile illness in people as well as reproductive losses in pigs. Pig keeping is an increasingly important livelihood to millions of smallholder farmers in Uganda because of exponential increases in demand for pork. The prevalence of leptospirosis and Q fever in pigs is unknown, and the few studies of porcine brucellosis have estimated a range of seroprevalence. Therefore, we undertook a prevalence survey of leptospirosis, brucellosis, and Q fever in pigs using quantitative real-time PCR to determine the potential importance of these zoonoses to the growing pig sector in Uganda. Six hundred forty-nine pigs were sampled in 2015–2016 at an urban pork slaughterhouse. Ten percent of pigs (n = 68) had leptospiral DNA in either their kidney or reproductive tissue. In adjusted analyses, variables predictive of leptospiral status included female sex (odds ratio [OR]: 2.37,P< 0.01) and pigs sampled in March 2016 (OR: 2.23,P= 0.02) and October 2016 (OR: 0.30,P= 0.04). DNA fingerprinting revealed circulation of at least four distinct serovars in these pigs. Brucella spp. and Coxiella burnetii DNA were not detected in any sampled pig. This is the first report of widespread circulation of pathogenic Leptospira spp. in pigs in Uganda, suggesting that leptospirosis likely has a greater impact on the health of pigs than was previously recognized. Pig farmers, pig traders, and slaughterhouse workers may be at greatest occupational risk because of their direct contact with infective leptospires in aborted fetuses, bodily fluids, and other tissues.